Integrated Approach to Migraine Management: A narrative review of the Pillars of Lifestyle Medicine - Dantas, Maria Ivone Oliveira; Carneiro, Narel Moita; Abib, Suellen (Headache Medicine, 2024)
IntroductionMigraine is a debilitating neurological disorder characterized by recurrent episodes of severe headaches, often accompanied by nausea and other autonomic symptoms. It affects a significant portion of the global population, with estimates suggesting a prevalence of approximately 58.2%. Beyond the immediate pain and discomfort, migraine can have a substantial impact on quality of life and productivity. Lifestyle medicine, which emphasizes the power of modifiable lifestyle factors to prevent, manage, and potentially reverse chronic diseases, offers a promising approach to migraine management.ObjectiveThis narrative review aims to map recent findings on the potential of lifestyle medicine pillars as effective strategies for managing migraine.MethodsA comprehensive narrative review was conducted using the PubMed database. Articles published within the past 10 years that investigate the intersection of migraine and lifestyle medicine were included.ResultsInterventions such as diet, physical exercise, stress management, sleep quality, healthy relationships, and cessation of alcohol and smoking can reduce the frequency and severity of attacks.ConclusionThis review highlights the potential of lifestyle medicine strategies to improve the management of migraine. By integrating interventions focused on diet, physical activity, stress management, sleep hygiene, healthy relationships, and substance cessation, migraine sufferers may experience a significant reduction in attack frequency and severity, ultimately leading to an enhanced quality of life.